2017
DOI: 10.1038/s41598-017-02827-5
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of the model system between phytochemicals and gene expression profiles in Macrosclereid cells of Medicago truncatula

Abstract: Macrosclereid cells, which are a layer in the seed coat of Medicago truncatula, accumulate large amounts of phytochemicals during their development. But little is known about the complex and dynamic changes during macrosclereid cell development. To characterize the phytochemicals and the related gene expression during the development of M. truncatula macrosclereid cells, a high performance liquid chromatography-mass spectrometry (HPLC-MS) assay and microarray study were conducted on transcriptome changes from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 102 publications
1
14
0
Order By: Relevance
“…Most commonly, studies have pointed out that the macrosclereid cell layer controls the water entry [ 13 ] and M. truncatula mutants with a defective outer cell layer differentiation, and in particular cuticle deposition, have supported this [ 49 ]. Cells of the macroslereid layer are rich in secondary metabolites and correlations between pigmentation and SC permeability were shown [ 13 , 19 , 41 ]. Analysis of the chemical composition of pea SC showed that polysaccharides, such as hemicellulose, cellulose, and especially pectins, comprise the largest proportion and their deposition is developmentally regulated [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most commonly, studies have pointed out that the macrosclereid cell layer controls the water entry [ 13 ] and M. truncatula mutants with a defective outer cell layer differentiation, and in particular cuticle deposition, have supported this [ 49 ]. Cells of the macroslereid layer are rich in secondary metabolites and correlations between pigmentation and SC permeability were shown [ 13 , 19 , 41 ]. Analysis of the chemical composition of pea SC showed that polysaccharides, such as hemicellulose, cellulose, and especially pectins, comprise the largest proportion and their deposition is developmentally regulated [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Legume seed development has been studied in Medicago truncatula Gaertn. [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ] and cultivated pea [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. Early in development, legume SC is a transient storage organ, which accumulates starch and proteins before storage activity starts in the embryo.…”
Section: Introductionmentioning
confidence: 99%
“…To link identified QTNs with putative causal gene by considering the linkage disequilibrium (LD), we selected all SNPs correlated (r 2 > 0.7) with the top identified QTNs within a 15kb genomic range, corresponding to the average LD block size present in the Medicago Hapmap population [100,102], and we listed gene IDs closely related to these SNPs. Seed expression pattern of the candidate genes was assessed using published Medicago seeds or seed coat expression studies [103,104] and web-based expression atlas [105]…”
Section: Genome-wide Association Analysismentioning
confidence: 99%
“…Its members are involved in the regulation of development, metabolism, the circadian rhythm, and responses to biotic and abiotic stresses in plants [74,79,80]. In Medicago truncatula multiple MYB TFs including MYB4 and MYB61 are involved in flavonoid biosynthesis during macrosclereid cell development [81]. MYB4 in particular regulates abiotic stress responses towards UV-B light and cadmium toxicity in Arabidopsis thaliana [82,83] and cold in Oryza sativa [84].…”
Section: Functional Analysis Of the Candidate Gene And Transcription mentioning
confidence: 99%